2019
DOI: 10.1016/j.jpain.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Antinociceptive Cross-Tolerance With Co-Administration of Morphine and Fentanyl Into the Periaqueductal Gray of Male Sprague-Dawley Rats

Abstract: Tolerance to the antinociceptive effect of mu-opioid receptor (MOPr) agonists, such as morphine and fentanyl, greatly limits their effectiveness for long-term use to treat pain. Clinical studies have shown that combination therapy and opioid rotation can be used to enhance opioid-induced antinociception once tolerance has developed. The mechanism and brain regions involved in these processes are unknown. The purpose of this study was to evaluate the contribution of the ventrolateral periaqueductal gray (vlPAG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In the present study, we observed that when morphine pretreated mice were challenged with either fentanyl or morphine, the degree of cross tolerance to fentanyl was less than the tolerance to morphine itself. A similar reduced level of cross tolerance between fentanyl and morphine has been reported in studies of rodent locomotor activity (Brase, ) and antinociception (Bobeck, Schoo, Ingram, & Morgan, ; Paronis & Holzman, ), although one study has reported equal cross tolerance between morphine and fentanyl on antinociception (Romero, Miranda, & Puig, ). Cross tolerance develops between drugs acting at the same receptor, but the degree of cross tolerance will depend upon agonist intrinsic efficacy.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, we observed that when morphine pretreated mice were challenged with either fentanyl or morphine, the degree of cross tolerance to fentanyl was less than the tolerance to morphine itself. A similar reduced level of cross tolerance between fentanyl and morphine has been reported in studies of rodent locomotor activity (Brase, ) and antinociception (Bobeck, Schoo, Ingram, & Morgan, ; Paronis & Holzman, ), although one study has reported equal cross tolerance between morphine and fentanyl on antinociception (Romero, Miranda, & Puig, ). Cross tolerance develops between drugs acting at the same receptor, but the degree of cross tolerance will depend upon agonist intrinsic efficacy.…”
Section: Discussionsupporting
confidence: 67%
“…Even though morphine and fentanyl are two of the most commonly used opioids to treat pain, morphine and fentanyl appear to engage different signalling pathways when microinjected into the periaqueductal gray (PAG). Antinociception produced by PAG morphine administration has a slower onset and longer duration than fentanyl (Bobeck, McNeal, & Morgan, ), is disrupted by blocking G‐protein signalling by administration of pertussis toxin whereas fentanyl antinociception is not (Bobeck, Ingram, Hermes, Aicher, & Morgan, ; Bodnar, Paul, Rosenblum, Liu, & Pasternak, ), and does not show cross‐tolerance to fentanyl following repeated PAG microinjections (Bobeck, Haseman, Hong, Ingram, & Morgan, ; Bobeck, Schoo, Ingram, & Morgan, ). These differences between morphine and fentanyl could be caused by selective activation of distinct signalling pathways or selective activation of pre‐ or postsynaptic MORs.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing effects of fentanyl increase in morphine-withdrawn rats, reflected by a rightward shift of the fentanyl dose-response curve with an increase in maximal effectiveness, whereas the reinforcing effects of fentanyl decrease in opioid-dependent rats [ 33 ]. However, no antinociceptive cross-tolerance occurs with repeated microinjections of morphine and fentanyl into the ventrolateral periaqueductal gray, which may be attributable to the different signaling mechanisms that mediate morphine- and fentanyl-induced antinociception [ 34 , 35 ].…”
Section: Fentanyl Abuse and Withdrawalmentioning
confidence: 99%